MAPS: the business of medical affairs - du Plessis, Danie (Henry Stewart Talks, 2023)
Medical Affairs Professional Society (MAPS), R&D, Commercialization, Strategic leadership, Pharmaceutical industry, Funding, Patient care, Industry partnership program, Health equity, DEI, ESG, Affordability, Ethics, Professional standards, Unmet needs, Patient outcomes, Real world evidence, Healthcare system, Medical affairs profession